A MoS based on alkylamine intercalation 2 / C composite material and its preparation method and application

The alkylamine intercalation and carbon substrate are combined by secondary hydrothermal method to form a MoS2/C composite material, which solves the problems of poor circulation performance and insufficient capacity of MoS2 in secondary batteries, and achieves efficient sodium ion storage and significantly improves battery performance.

CN118851264BActive Publication Date: 2025-04-08WUHAN INST OF TECH

Patent Information

Application Number
CN202410908593.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2025-04-08
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

When the existing MoS2 is used as the negative electrode material for secondary batteries, there are problems such as poor circulation performance, insufficient capacity and volume expansion effects, which limits its application in sodium ion battery energy storage.

Method used

By performing alkylamine intercalation by secondary hydrothermal method, the layer spacing of MoS2 is expanded and composited with the carbon substrate to form a stable MoS2/C composite material. This method overcomes the thermodynamic limitations during the intercalation process, enhances the intercalation effect, and provides better conductivity and structural stability.

Benefits of technology

It significantly improves the electron conductivity and structural stability of MoS2, establishes a dual continuous channel of ions and electrons, greatly solves the demand for efficient sodium ion storage, and effectively improves the specific capacity and cycling performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851264B_ABST
    Figure CN118851264B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of secondary battery energy storage, and in particular to a MoS2 / C composite material based on alkylamine intercalation and its preparation method and application, the method comprising: dispersing molybdate and thiourea in deionized water, adding hydrochloric acid, stirring and performing a first hydrothermal reaction; mixing the sample obtained by the first hydrothermal reaction with hydrochloric acid, adding an alkylamine compound, performing a second hydrothermal reaction, and obtaining a MoS2 / C precursor; drying and sintering the MoS2 / C precursor to obtain a MoS2 / C composite material. The composite material prepared by the preparation method of the present invention has a stable and reliable support structure, which can prevent the structural deterioration of molybdenum disulfide and significantly improve the conductivity of electrons. A double continuous channel is established between ions and electrons, which greatly solves the demand for efficient sodium ion storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery energy storage, in particular to a MoS based on alkylamine intercalation. 2 / C composite material and its preparation method and application. Background Art

[0002] The development of energy storage technology provides support for the popularization and utilization of renewable clean energy, and effectively solves a series of problems such as energy crisis and increased environmental pollution. As a key energy storage technology, secondary batteries have broad application prospects in electric vehicles and renewable energy storage. In recent years, finding a suitable negative electrode material to improve battery performance has become a hot topic.

[0003] The negative electrode materials of traditional lithium and sodium secondary batteries are mostly graphite, hard carbon, etc., but their low capacity is not enough to meet the application requirements of ultra-high energy density. 2 It is a typical two-dimensional material with a layered structure. Each layer of molybdenum disulfide consists of a molybdenum (Mo) atom sandwiched between two sulfur atoms (S), forming a three-layer structure. Thanks to this layered structure, MoS 2 As a negative electrode material for batteries, MoS has shown high theoretical capacity and excellent electrochemical performance, making it a widely studied negative electrode material. However, in practical applications, MoS 2 The poor cycle performance and low capacity as negative electrode materials, as well as their inherent volume expansion effect and low conductivity, limit their application in secondary battery energy storage.

[0004] In Chinese patent CN 103275355 A, the synthesized organically modified molybdenum disulfide nanosheets can expand the interlayer spacing, but the intercalation agents used in the synthesis process, such as n-butyl lithium and lithium hydride, are dangerous to a certain extent. Chinese patent 202111072455.0 uses nitrogen-doped carbon intercalation, which solves the problem of capacity and volume effect, but its lack of reaction control and other factors still limit its practical application.

[0005] Chinese Patent 202410069521.6 discloses a nanosheet cluster material of methylamine ion intercalation mixed phase molybdenum disulfide. The methylamine intercalation in this patent is just a simple molybdenum disulfide intercalation, and the composite of molybdenum disulfide and carbon is not achieved. Simply mixing cannot achieve a good conductive effect. This material is used in this catalytic aspect (lithium oxygen battery); Chinese Patent 201910225159.6 discloses a method for preparing a molybdenum disulfide composite molybdenum dioxide material for sodium ion negative electrode material, which is significantly different from the synthetic molybdenum disulfide composite carbon substrate we use. The key point is that the nanosheets overlap each other to form a three-dimensional space, and the thickness, length and other factors of the molybdenum disulfide molybdenum dioxide composite material affect its material stability. And as a negative electrode material for sodium ion batteries, the final test results show that the effect is obviously not increased, the capacity is obviously insufficient, and the optimal capacity can only maintain about 380mA g -1 .

[0006] Using alkylamines to intercalate MoS2 to expand the interlayer is an effective method to promote ion insertion and extraction and improve the intrinsic capacity of layered materials. However, since the intercalation effect may be affected by factors such as repulsion, MoS 2 The process of interlayer intercalation may be thermodynamically limited. Summary of the invention

[0007] In order to solve the above problems, the present invention aims to provide a MoS based on alkylamine intercalation. 2 / C composite material and its preparation method and application. The present invention can overcome this thermodynamic limitation and enhance the intercalation effect by a secondary hydrothermal method; alkylamine, as a long-chain molecule, can form a stable interlayer-enlarged molybdenum disulfide after hydrothermal treatment compared with common ammonium salts; the carbon chain in the alkylamine is compounded with the intercalated molybdenum disulfide to form a carbon substrate in situ after carbonization, and with the help of the flexibility and conductivity of the carbon material, MoS 2 Providing a more stable and reliable support structure, preventing the structural deterioration of molybdenum disulfide while significantly improving the conductivity of electrons, while providing a fast transmission channel for ions and electrons, greatly solving the need for efficient sodium ion storage. 2 The electrochemical performance of the negative electrode of the sodium battery is improved, and the relevant strategies for solving this problem are further optimized. To achieve the above purpose, the present invention provides the following technical solutions:

[0008] A MoS based on alkylamine intercalation 2 A method for preparing a / C composite material, the method comprising:

[0009] Disperse molybdate and thiourea in deionized water, add hydrochloric acid, and stir to carry out the first hydrothermal reaction;

[0010] The sample obtained by the first hydrothermal reaction was mixed with hydrochloric acid, and an alkylamine compound was added to perform a second hydrothermal reaction to obtain MoS 2 / C precursor;

[0011] The MoS 2 / C precursor is dried and sintered to obtain MoS 2 / C composite material.

[0012] Furthermore, the molar ratio of the molybdate to thiourea is 1:30.

[0013] Furthermore, the molybdate includes ammonium molybdate tetrahydrate, sodium molybdate or potassium molybdate.

[0014] Furthermore, the conditions of the first hydrothermal reaction are: reaction temperature 140-200° C., time 12-48 h.

[0015] Furthermore, the molar ratio of the sample obtained by the first hydrothermal reaction to the alkylamine compound is 1:1; the alkylamine compound includes one of tetradecylamine, hexadecylamine or octadecylamine.

[0016] Furthermore, the conditions of the second hydrothermal reaction include a reaction temperature of 140 to 200° C. and a time of 12 to 48 hours.

[0017] Furthermore, the MoS 2 / C precursor is dried and sintered, including:

[0018] The MoS 2 / C precursor is dried at a temperature of 60-80°C for 24-48h;

[0019] The dried product is sintered in a protective atmosphere at a sintering temperature of 600-900° C. and a heat preservation time of 2-3 hours.

[0020] Furthermore, the protective atmosphere comprises a hydrogen-argon mixed gas, wherein the content of hydrogen is 5-10% and the rest is argon.

[0021] A MoS based on alkylamine intercalation 2 / C composite material, which is obtained by adopting the preparation method.

[0022] The alkylamine intercalated MoS obtained by the preparation method described above 2 Application of / C composite materials in negative electrode materials of sodium ion batteries.

[0023] Technical effects and advantages of the present invention:

[0024] This application proposes a method for intercalating molybdenum disulfide to expand the interlayer spacing and composite it with a carbon substrate. By using alkylamine to intercalate molybdenum disulfide, stable interlayer expansion of molybdenum disulfide is achieved. At the same time, the carbon in the in-situ alkylamine can provide a carbon substrate for the material, reduce the structural fission of the material during the insertion and extraction of sodium ions, and at the same time have conductivity, realizing a dual continuous channel for ions and electrons.

[0025] An alkylamine intercalated MoS 2 The secondary hydrothermal preparation method of the MoS2 / C composite material can more effectively overcome the thermodynamic limitations such as repulsion that may occur during the intercalation process, open the interlayer, and thus enhance the effect. At the same time, while avoiding the use of more dangerous intercalation agents such as n-butyl lithium, the intercalation effect is more effectively enhanced through two hydrothermal treatments. It also greatly improves the safety and universality of the MoS2 intercalation process, and is easier to promote in practical applications and industrialization, and has broad application prospects.

[0026] The composite material prepared by the preparation method of the present invention has a stable and reliable support structure, which can prevent the structural deterioration of molybdenum disulfide and significantly improve the conductivity of electrons. A double continuous channel is established between ions and electrons, which greatly solves the demand for efficient sodium ion storage.

[0027] Compared with traditional lithium-ion batteries, sodium-ion batteries have the advantages of high energy density, high safety and low cost, but due to the large diameter of sodium ions, the electrochemical reaction kinetics are limited, which leads to problems such as low reversible capacity and rapid capacity decay. The negative electrode material in the present invention is applied to sodium-ion batteries. Since the interlayer spacing in the negative electrode material is enlarged, the enlarged interlayer spacing is also more conducive to the transportation of sodium ions. Alkylamines are intercalated in situ, providing a carbon substrate, reducing resistance and preventing structural degradation, and establishing a dual continuous channel between ions and electrons, which greatly solves the demand for efficient sodium ion storage. Its application in sodium-ion batteries can effectively solve the problems of low specific capacity and poor cycle performance.

[0028] The present invention uses alkylamine intercalation to achieve the regulation of interlayer spacing, thereby expanding the interlayer spacing and realizing MoS 2 The conductivity is significantly enhanced when combined with carbon.

[0029] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1aThe SEM image 1 of the composite material obtained in Example 1 is shown;

[0031] Figure 1b The SEM of the composite material obtained in Example 1 is shown. Figure 2 ;

[0032] Figure 2 TEM image of the composite material obtained in Example 1 is shown;

[0033] Figure 3 shows a SEM image of the composite material obtained in Example 2;

[0034] Figure 4 TEM image of the composite material obtained in Example 2 is shown;

[0035] Figure 5 The SEM image of the composite material obtained in Example 3 is shown;

[0036] Figure 6 TEM image of the composite material obtained in Example 3 is shown;

[0037] Figure 7 shows a SEM image of the composite material obtained in Example 4;

[0038] Figure 8 TEM image of the composite material obtained in Example 4 is shown;

[0039] Fig. 9 The SEM image of the composite material obtained in Comparative Example 1 is shown;

[0040] Fig.10 The TEM image of the composite material obtained in Comparative Example 1 is shown;

[0041] Fig.11 The SEM image of the composite material obtained in Comparative Example 2 is shown;

[0042] Fig.12 The TEM image of the composite material obtained in Comparative Example 2 is shown;

[0043] Fig.13 The XRD comparison diagrams of Example 1, Example 4, Comparative Example 1 and Comparative Example 2 are shown;

[0044] Fig.14 The Raman comparison diagram of the composite material of Example 1 and Comparative Example 1 is shown;

[0045] Fig.15 A battery specific capacity comparison diagram is shown, wherein a represents the battery specific capacity of Example 1; b represents the battery specific capacity of Example 4; c represents the battery specific capacity of Comparative Example 1; and d represents the battery specific capacity of Comparative Example 2;

[0046] Fig.16 The cycle performance diagram of the composite material obtained in Example 1 using a sodium sheet as a half-cell is shown;

[0047] Fig.17 The cycle performance diagram of the composite material obtained in Comparative Example 1 using a sodium sheet as a half-cell is shown. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] In order to solve the shortcomings of the prior art, the present invention discloses a MoS based on alkylamine intercalation 2 A method for preparing a / C composite material, the method comprising:

[0050] Step 1: Disperse molybdate and thiourea in deionized water, add hydrochloric acid, stir and perform the first hydrothermal reaction to obtain MoS 2 / C precursor;

[0051] Step 2: After mixing the sample obtained by the first hydrothermal reaction with hydrochloric acid, an alkylamine compound is added to perform a second hydrothermal reaction to obtain MoS 2 / C precursor;

[0052] Step 3: The MoS 2 / C precursor is dried and sintered to obtain MoS 2 / C composite material.

[0053] In a specific embodiment of the present invention, in step 1, the specific steps are as follows:

[0054] Ammonium molybdate tetrahydrate and thiourea are dispersed in deionized water, hydrochloric acid is added, and the first hydrothermal reaction is carried out after stirring. The conditions of the first hydrothermal reaction are 140-200° C. and the hydrothermal time is 12-48 hours. Under this condition, it is easier to overcome the thermodynamic limitation and expand the interlayer distance.

[0055] The molar ratio of molybdate to thiourea is 1:30;

[0056] The molybdate includes ammonium molybdate tetrahydrate, sodium molybdate or potassium molybdate.

[0057] In a specific embodiment of the present invention, in step 2, the specific steps are as follows:

[0058] The sample obtained by the first hydrothermal reaction was mixed with hydrochloric acid, and then dispersed with alkylamine in deionized water and ultrasonicated. The ultrasonic power was 700W and the ultrasonic time was 20min. Under this ultrasonic condition, a more uniform dispersion effect can be obtained, and the use of hexadecylamine can better achieve hydrothermal intercalation.

[0059] Then it was transferred to the reactor for a second hydrothermal reaction to obtain MoS 2 / C precursor; the conditions of the second hydrothermal reaction are 140-200°C, and the hydrothermal time is 12-48h. Under this condition, the interlayer can be further expanded and the intercalation effect of the alkylamine can be enhanced.

[0060] In a specific embodiment of the present invention, in step 3, the specific steps are as follows:

[0061] The MoS 2 / C precursor is dried at a temperature of 60-80°C for 24-48h;

[0062] The dried product is sintered in a protective atmosphere at a temperature of 600-900°C, preferably 700°C, for 2-3 hours to obtain alkylamine intercalated MoS 2 / C composite material.

[0063] Preferably, the product after the second hydrothermal reaction is dried at 700°C and then sintered in a protective atmosphere, wherein the protective atmosphere is a hydrogen-argon mixture, the heating rate is 5°C / min, the sintering temperature is 700°C, and the holding time is 2h. Under this condition, it is easier to obtain MoS with uniform dispersion of the three elements S, C, and Mo. 2 / C composite material.

[0064] The composite material prepared by the preparation method of the present invention has a stable and reliable support structure, which can prevent the structural deterioration of molybdenum disulfide and significantly improve the conductivity of electrons. A double continuous channel is established between ions and electrons, which greatly solves the demand for efficient sodium ion storage.

[0065] In a specific embodiment of the present invention, the protective atmosphere comprises a hydrogen-argon mixed gas, wherein the content of hydrogen is 5-10% and the rest is argon, the inert gas is used as the sintering protective gas, and the hydrogen is used as the reducing atmosphere.

[0066] MoS 2 The molar ratio of the / C precursor to the alkylamine compound is 1:1, preferably 1 mmol:1 mmol.

[0067] The alkylamine compound includes one of tetradecylamine, hexadecylamine or octadecylamine.

[0068] An alkylamine intercalated MoS 2The secondary hydrothermal preparation method of the / C composite material can more effectively overcome the thermodynamic limitations such as repulsion that may occur during the intercalation of alkylamines, open the interlayers, and enhance the effect. At the same time, the intercalation effect is more effectively enhanced by two hydrothermal treatments while avoiding the use of more dangerous intercalation agents such as n-butyl lithium. It also greatly improves the safety and universality of the molybdenum disulfide intercalation process, and is easier to promote in practical applications and industrialization, and has broad application prospects.

[0069] The present invention adopts the hydrothermal reaction conditions in step 1 and step 2 to prepare a molybdenum disulfide negative electrode material with good alkylamine intercalation effect and excellent interlayer expansion effect. If the reaction conditions are not met, the MoS2 intercalated with alkylamine in the present invention cannot be prepared. 2 / C composite material, and the prepared material cannot achieve the effect of the present invention.

[0070] The composite material prepared by the preparation method of the present invention has a stable and reliable support structure, which can prevent the structural deterioration of molybdenum disulfide and significantly improve the conductivity of electrons. A double continuous channel is established between ions and electrons, which greatly solves the demand for efficient sodium ion storage.

[0071] The use of the composite material of the present invention as negative electrode material can effectively solve the problems of low specific capacity and poor cycle performance.

[0072] Compared with traditional lithium-ion batteries, sodium-ion batteries have the advantages of high energy density, high safety and low cost. However, due to the large diameter of sodium ions, the electrochemical reaction kinetics are limited, which leads to problems such as low reversible capacity and rapid capacity decay. The negative electrode material in the present invention is applied to sodium-ion batteries. Since the interlayer spacing in the negative electrode material is enlarged, the enlarged interlayer spacing is also more conducive to the transport of sodium ions. Alkylamines are intercalated in situ to provide a carbon substrate, reduce resistance and prevent structural degradation, and establish a dual continuous channel between ions and electrons, which greatly solves the need for efficient sodium ion storage. Its application in sodium-ion batteries can effectively solve the problems of low specific capacity and poor cycle performance. The present invention also discloses a MoS based on alkylamine intercalation. 2 / C composite material, obtained by the above-mentioned preparation method.

[0073] The present invention also discloses an alkylamine intercalated MoS obtained by the preparation method as described above. 2 Application of the C / C composite material in a negative electrode material for a sodium ion battery. Preferably, the negative electrode material is used in a secondary battery, wherein the secondary battery is a sodium ion battery.

[0074] Compared with traditional lithium-ion batteries, sodium-ion batteries have the advantages of high energy density, high safety and low cost, but due to the large diameter of sodium ions, the electrochemical reaction kinetics are limited, which leads to problems such as low reversible capacity and rapid capacity decay. The negative electrode material in the present invention is applied to sodium-ion batteries. Since the interlayer spacing in the negative electrode material is enlarged, the enlarged interlayer spacing is also more conducive to the transportation of sodium ions. Alkylamines are intercalated in situ, providing a carbon substrate, reducing resistance and preventing structural degradation, and establishing a dual continuous channel between ions and electrons, which greatly solves the demand for efficient sodium ion storage. Its application in sodium-ion batteries can effectively solve the problems of low specific capacity and poor cycle performance.

[0075] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0076] Example 1

[0077] 1.366 g of ammonium molybdate tetrahydrate ((NH 4 ) 6 Mo 7 O 24 ·4H 2 O) and 2.534 g thiourea (CH 4 N 2 S) was evenly dispersed in deionized water, and 100 1L 6M HCl solution was added, magnetic stirring was performed for 1h, and then placed in a 100mL polytetrafluoroethylene-lined and stainless steel autoclave, and the first hydrothermal reaction was performed at 180°C for 24h. After cooling, the product was taken out, and the product was centrifuged and washed three times with deionized water, ethanol, and deionized water, and then dried in a constant temperature drying oven at 70 degrees for 24h to obtain the sample.

[0078] The sample obtained by the first hydrothermal reaction after drying was placed in an agate mortar and 100

[0079] L 6M HCl solution, grind for 10 minutes. Weigh 0.16g of the ground sample obtained by the first hydrothermal reaction, and then weigh 0.241g of hexadecylamine (0.001mol), 40mL of deionized water, and ultrasonicate for 30min at a power of 100W in an ultrasonic cleaner to disperse evenly. Place the above mixture in a 100mL polytetrafluoroethylene-lined and stainless steel autoclave, and perform the second hydrothermal reaction at 180℃ for 24h. After cooling, take it out, collect the precipitate, and centrifuge and wash the sample three times with deionized water to obtain MoS 2 / C precursor. 2 The precursor was dried in a 70°C constant temperature oven for 24 h and then placed in a tube furnace and introduced with a hydrogen-argon mixture (5% H 2 ), and then heated to 700°C at 5°C / min and kept at this temperature for 2h to obtain MoS2 / C composite material.

[0080] The hexadecylamine intercalated MoS 2 / C composite material, denoted as MoS 2 / C-16, conductive carbon black (acetylene black) and polyvinylidene chloride (PVDF) were mixed in a mass ratio of 7:2:1, stirred for 24 hours, and ultrasonically treated for 1 hour to obtain a uniformly dispersed electrode slurry for preparing a working electrode, which was assembled in a 2025-button cell for testing. The above slurry was coated on a clean copper foil surface with a thickness of 2000 microns and punched into a 10mm diameter disc as a working electrode. A sodium sheet with a diameter of 14mm was used as the counter electrode, and a glass fiber filter paper (GF / A) with a diameter of 17mm was used as a diaphragm. The electrolyte was 1M NaClO 4 in DEC:EC=1:1Vo l%with 5%FEC. Constant current charge / discharge test was performed on the Blue Power Battery Test System with a voltage range of (0.01-0.3V).

[0081] Figure 1a-1b The MoS obtained in this example is shown 2 SEM images of / C-16 composite materials, Figure 2 The MoS obtained in this example is shown 2 TEM images of MoS / C-16 composites 2 / C presents a stacked and layered flake structure. High-resolution transmission electron microscopy images show that MoS 2 / C composite material interlayer spacing is 1.02-1.03nm, which is consistent with the XRD pattern.

[0082] Example 2

[0083] The sample was prepared by the same secondary hydrothermal method as in Example 1. However, the secondary hydrothermal conditions were all at 160°C for 48 hours. The sample was placed in a tube furnace, a hydrogen-argon mixed gas (5%) was introduced, and the temperature was raised to 700°C at 5°C / min and kept at this temperature for 2 hours to obtain MoS 2 / C composite material.

[0084] The hexadecylamine intercalated MoS 2 / C composite material, and assembled a sodium ion battery in the same manner as in Example 1, and performed a battery performance test in the same manner.

[0085] Figure 3 The MoS obtained in this example is shown 2 / C-16-160℃ composite material SEM image, it can be seen that the MoS 2 / C composite materials present a three-dimensional nanoflower structure.

[0086] Figure 4 The MoS obtained in this example is shown 2 TEM image of MoS / C-16-160℃ composite material 2 / C composite material interlayer spacing is 0.994-1.22nm.

[0087] Example 3

[0088] The first hydrothermal reaction was carried out under the same conditions as in Example 1 to obtain the sample after the first hydrothermal reaction. Take the sample obtained by the first hydrothermal reaction after drying, place it in an agate mortar, add 100 1L 6M HCl solution, and grind for 10 minutes. Weigh 0.16g of the ground sample obtained by the first hydrothermal reaction, and then weigh 0.213g of tetradecamine (0.001mol), 40mL of deionized water, and in an ultrasonic cleaner, ultrasonicate for 30min at a power of 100W to disperse evenly. The above mixed solution was placed in a 100mL polytetrafluoroethylene-lined and stainless steel high-pressure reactor, and the second hydrothermal reaction was carried out at 180°C for 24h. After cooling, take it out, collect the precipitate, and wash the sample three times with deionized water by centrifugation to obtain MoS 2 / C precursor. 2 The / C precursor was dried in a 70°C constant temperature drying oven for 24 h, then placed in a tube furnace, introduced with a hydrogen-argon mixture (5%), and heated to 700°C at a rate of 5°C / min and kept at that temperature for 2 h to obtain MoS 2 / C composite material, denoted as MoS 2 / C-14.

[0089] The battery performance test method is the same as that in Example 1.

[0090] Figure 5 The MoS obtained in this example is shown 2 SEM image of / C-14-180℃ composite material, Figure 6 The MoS obtained in this example is shown 2 TEM image of / C-14-180℃ composite material, MoS 2 / C composite material interlayer spacing is 1.02-1.12nm.

[0091] Example 4

[0092] The first hydrothermal reaction was carried out under the same conditions as in Example 1 to obtain the sample. Take the sample obtained by the first hydrothermal reaction after drying, place it in an agate mortar, add 100 1L 6M HCl solution, and grind for 10 minutes. Weigh 0.16g of the ground sample obtained by the first hydrothermal reaction, and then weigh 0.241g of hexadecylamine (0.001mol), 40mL of deionized water, and ultrasonicate for 30min at a power of 100W in an ultrasonic cleaner to disperse evenly. The above mixed solution was placed in a 100mL polytetrafluoroethylene-lined and stainless steel high-pressure reactor, and the second hydrothermal reaction was carried out at 180°C for 24h. After cooling, take it out and collect the precipitate to obtain MoS after the second hydrothermal reaction. 2 / C precursor; MoS after the second hydrothermal reaction 2 The / C precursor and 0.241 g of hexadecylamine (0.001 mol) and 40 mL of deionized water were ultrasonically cleaned in an ultrasonic cleaning machine at a power of 100 W for 30 min to obtain a uniformly dispersed mixed solution;

[0093] The mixed solution was placed in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and subjected to a third hydrothermal reaction at 180°C for 24 h. After cooling, the mixture was taken out and the precipitate was collected and washed three times with deionized water by centrifugation to obtain MoS after the third hydrothermal reaction. 2 / C precursor. Then, the MoS 2 The precursor was dried in a 70°C constant temperature drying oven for 24 h, then placed in a tube furnace, introduced with a hydrogen-argon mixture (5%), and heated to 700°C at a rate of 5°C / min and kept at that temperature for 2 h to obtain MoS 2 / C composite material.

[0094] The battery performance test method is the same as that in Example 1.

[0095] Figure 7 The MoS obtained by three hydrothermal processes in this embodiment is shown in FIG. 2 SEM images of / C composites, Fig. 9 The MoS obtained by three hydrothermal processes in this embodiment is shown in FIG. 2 TEM images of MoS / C composites 2 / C composite material interlayer spacing is 1.05-1.22nm.

[0096] Comparative Example 1

[0097] A MoS 2 The primary hydrothermal preparation method for material interlayer expansion is as follows:

[0098] 1.366 g of ammonium molybdate tetrahydrate ((NH 4 ) 6 Mo 7 O24 ·4H 2 O) and 2.534 g thiourea (CH 4 N 2 S) was evenly dispersed in deionized water, and 100 1L 6M HCl solution was added, magnetically stirred for 1h, and then placed in a 100mL polytetrafluoroethylene-lined and stainless steel autoclave for the first hydrothermal treatment at 180°C for 24h. After cooling, the product was taken out and washed three times by centrifugation with deionized water, ethanol, and deionized water to obtain a sample. The sample was dried in a 70-degree constant temperature drying oven for 24h, and then heated to 700°C at 5°C / min in a tubular furnace with a hydrogen-argon mixed gas (5%) atmosphere, and kept warm for 2h to obtain MoS 2 / C composite material.

[0099] The MoS with enlarged interlayer obtained in this example 2 Materials, conductive carbon black (acetylene black) and polyvinylidene chloride (PVDF) were mixed in a mass ratio of 7:2:1, stirred for 24 hours, and ultrasonically treated for 1 hour to obtain a uniformly dispersed electrode slurry for preparing a working electrode, which was assembled on a 2016-button battery for testing. The above slurry was coated on the surface of a clean copper foil with a thickness of 2000 microns and punched into a 10mm diameter disc as a working electrode. A sodium sheet with a diameter of 14mm was used as the counter electrode, and a glass fiber filter paper (GF / A) with a diameter of 17mm was used as a diaphragm. The electrolyte was 1M NaClO 4 inDEC:EC=1:1Vol%with 5%FEC. Constant current charge / discharge test was performed on the Blue Power Battery Test System with a voltage range of (0.01-0.3V).

[0100] Fig. 9 The MoS obtained by one hydrothermal treatment without adding organic ammonium in this embodiment is shown in FIG. 2 SEM images of / C composites, Fig.10 The MoS obtained by one hydrothermal treatment without adding organic ammonium in this embodiment is shown in FIG. 2 The TEM image of the / C composite material shows a stacked and layered flaky structure. The high-resolution transmission electron microscopy image shows that it is the initial molybdenum disulfide precursor with an interlayer spacing of 0.62nm, which is the same as that in the reference.

[0101] Comparative Example 2

[0102] 1.366 g of ammonium molybdate tetrahydrate ((NH 4 ) 6 Mo 7 O 24 ·4H 2 O), 2.534 g thiourea (CH 4 N 2S) and 0.482g hexadecylamine were uniformly dispersed in deionized water, and 100L 6M HCl solution was added, magnetic stirring was performed for 1h, and then placed in a 100mL polytetrafluoroethylene-lined and stainless steel high-pressure reactor, and hydrothermal was performed once at 180°C for 24h. After cooling, the product was taken out and washed three times with deionized water, ethanol, and deionized water by centrifugation to obtain a sample. After the sample was dried in a 70-degree constant temperature drying oven for 24h, it was heated to 700°C at 5°C / min in a tubular furnace with a hydrogen-argon mixed gas (5%) atmosphere and kept warm for 2h to obtain MoS 2 / C composite material.

[0103] Fig.11 The MoS obtained by hydrothermal treatment in this embodiment is shown in FIG. 2 SEM images of / C composites, Fig.12 The MoS obtained in this example is shown 2 The TEM image of the / C composite material shows that the interlayer expansion effect is not obvious, only expanding from 0.62nm to 0.64m. The following descriptions are similar.

[0104] The battery performance test method is the same as that in Example 1.

[0105] Data description:

[0106] Fig.13 The XRD comparison diagrams of Example 1 (twice hydrothermal), Example 4 (three times hydrothermal), Comparative Example 1 and Comparative Example 2 are shown. The ordinate in the figure is the peak intensity and the abscissa is 2θ. It can be seen from the figure that the peaks of Examples 1 and 4 are significantly shifted to the left compared with Comparative Examples 1 and 2, indicating that the interlayer spacing is more significantly enlarged, which is caused by multiple hydrothermal intercalation of alkylamine. 2 The XRD diagram of Example 1 shows that the interlayer expansion effect is poor compared with that of Example 1.

[0107] Fig.14 It is shown that the distance between the two peaks E2g and A1 g of the composite material decreases after hexadecane intercalation, indicating that the layered structure of molybdenum disulfide is destroyed and the number of layers is reduced.

[0108] Fig.15 A battery specific capacity comparison diagram is shown, with the abscissa being the specific capacity and the ordinate being the voltage; wherein a represents the battery specific capacity of Example 1, and the composite material obtained in Example 1 shows a specific capacity diagram with a sodium sheet as a half-cell, which exhibits an ultra-high specific capacity of 800mAh / g at a current density of 1A / g; b represents the battery specific capacity of Example 4, which exhibits an ultra-high specific capacity of 1500mAh / g during the first three cycles of charge and discharge at a current density of 0.2A / g;

[0109] c represents the specific capacity of the battery of Comparative Example 1. At a current density of 0.2 A / g, it has a specific capacity of only about 150 mAh / g, and the second cycle decays significantly. Its specific capacity and cycle performance are significantly insufficient compared with those of Example 1.

[0110] d represents the specific capacity of the battery of Comparative Example 2. The specific capacity diagram of the composite material (one-time hydrothermal intercalation) obtained in this embodiment using a sodium sheet as a half-cell shows a specific capacity of less than 200 mAh / g at a current density of 0.2 A / g, which obviously cannot achieve the effect of the embodiment.

[0111] Fig.16 The graph of the cycle performance of the composite material obtained in Example 1 with a sodium sheet as a half-cell is shown, with the horizontal axis being the number of cycles, the left vertical axis being the specific capacity, and the right vertical axis being the coulombic efficiency; using the material as the negative electrode of a sodium ion battery, at a current density of 1A / g, after 500 cycles, the capacity decay is small and remains at about 80%; the graph of the specific capacity of the composite material obtained in Example 1 with a sodium sheet as a half-cell shows an ultra-high specific capacity of 800mAh / g at a current density of 1A / g.

[0112] Fig.17 The graph of the cycle performance of the composite material obtained in Comparative Example 1 with a sodium sheet as a half-cell is shown, with the horizontal axis representing the number of cycles, the left vertical axis representing the specific capacity, and the right vertical axis representing the coulombic efficiency. At a current density of 0.2 A / g, after 20 cycles, the specific capacity has decayed to less than 10 mAh / g, which obviously cannot achieve the effect of the embodiment.

[0113] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Application of MoS2 / C composite material based on alkylamine intercalation in negative electrode material of sodium ion battery, characterized in that: The preparation method of the MoS2 / C composite material based on alkylamine intercalation comprises: Dispersing molybdate and thiourea in deionized water, adding hydrochloric acid, stirring and performing a first hydrothermal reaction; the molar ratio of the molybdate to thiourea is 1:30; the molybdate includes ammonium molybdate tetrahydrate or potassium molybdate; After mixing the sample obtained by the first hydrothermal reaction with hydrochloric acid, an alkylamine compound is added to carry out a second hydrothermal reaction to obtain a MoS2 / C precursor; the conditions of the first hydrothermal reaction are: reaction temperature 140-200°C, time 12-48h; the molar ratio of the sample obtained by the first hydrothermal reaction to the alkylamine compound is 1:1; the alkylamine compound includes one of tetradecylamine, hexadecylamine or octadecylamine; the conditions of the second hydrothermal reaction include reaction temperature 140-200°C, time 12-48h; The MoS2 / C precursor is dried and sintered to obtain a MoS2 / C composite material; wherein the sintering is carried out in a protective atmosphere, the sintering temperature is 700-900°C, and the insulation time is 2-3h.

2. The use of a MoS2 / C composite material based on alkylamine intercalation in a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The MoS2 / C precursor is dried and sintered, comprising: The MoS2 / C precursor is dried at a temperature of 60-80°C. , The time is 24-48h.

3. The use of a MoS2 / C composite material based on alkylamine intercalation in a negative electrode material for a sodium ion battery according to claim 2, characterized in that: The protective atmosphere comprises a hydrogen-argon mixed gas, wherein the content of hydrogen is 5-10% and the rest is argon.

Citation Information

Patent Citations

  • Organic modified molybdenum disulfide nanosheet layer and preparation method thereof

    CN103275355A

  • Method for preparing molybdenum disulfide / molybdenum dioxide composite material used for sodium ion negative electrode material

    CN110048095A

  • Nitrogen-doped carbon intercalation molybdenum disulfide sodium ion battery negative electrode and preparation method thereof

    CN113921763A

  • Nanosheet cluster material of methylamine ion intercalation mixed-phase molybdenum disulfide, preparation method of nanosheet cluster material and application of nanosheet cluster material in lithium oxygen battery

    CN117895012A

  • Ultra-large interlayer spacing molybdenum disulfide / carbon composite material and preparation method of molybdenum disulfide / carbon composite material

    CN111111702A

Cited By

  • Alkali metal ion intercalation molybdenum disulfide and preparation method and application thereof

    CN121426173A